Haemorrhage and coagulopathy in the Defence Medical Services. (4th December 2012) - Mercer, S. J.; Tarmey, N. T.; Woolley, T.; Wood, P.; Mahoney, P. F.
Summary: Over the past 12 years, the United Kingdom Defence Medical Services have evolved an integrated 'damage control resuscitation – damage control surgery' sequence for the management of patients sustaining complex injuries. During 2009, over 3200 units of blood products were administered as massive transfusions to severely injured UK personnel. An important part of the approach to traumatic bleeding is the early, empirical use of predefined ratios of blood and clotting products. As soon as control of bleeding is achieved, current practice is to switch towards a tailored transfusion, based on clinical and laboratory assessments, including point‐of‐care coagulation testing. A key goal is to provide resuscitation seamlessly throughout surgery, so that patients leave the operating room with their normal physiology restored. This article outlines the current management of haemorrhage and coagulation employed in Afghanistan from the point of wounding to transfer back to the National Health Service.